2019
DOI: 10.1016/j.jeoa.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Transfers in an aging European Union

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…With increasingly flexible later-life working arrangements, the cut-off of 65 years of age is progressively becoming less descriptive of a population's real productivity (Vaupel and Loichinger 2006;Lee et al 2014). Ideally, we would want to use estimates for population consumption and production age curves at regional level, similar to the National Transfer Accounts estimated for countries (Kupiszewski 2013;Vargha et al 2017;Kluge et al 2019). Unfortunately, these estimates are not yet available at the regional level, which is the focus of this study on urban-rural differences.…”
Section: Discussionmentioning
confidence: 99%
“…With increasingly flexible later-life working arrangements, the cut-off of 65 years of age is progressively becoming less descriptive of a population's real productivity (Vaupel and Loichinger 2006;Lee et al 2014). Ideally, we would want to use estimates for population consumption and production age curves at regional level, similar to the National Transfer Accounts estimated for countries (Kupiszewski 2013;Vargha et al 2017;Kluge et al 2019). Unfortunately, these estimates are not yet available at the regional level, which is the focus of this study on urban-rural differences.…”
Section: Discussionmentioning
confidence: 99%
“…Various theoretical and empirical studies have shown that population ageing – that is, changes in the population age structure that result in a shrinking relative size of the working age population – has a negative effect on economic growth (Bloom & Williamson ; Prskawetz et al ; Bloom et al ; Crespo Cuaresma et al ; van der Gaag & De Beer ). A decline in the size of the working age population has a downward effect on GDP per capita, whereas an increase in the number of elderly citizens has an upward effect on costs of pensions and care (Kluge ; van Nimwegen ; Kluge et al ). Other things equal, a decrease in the share of the working age population slows down the economic growth of a region (Teixeira et al ).…”
Section: Theoretical Considerations and The Proposed Frameworkmentioning
confidence: 99%
“…changes in the population age structure that result in a shrinking relative size of the working age population -has a negative effect on economic growth (Bloom and Williamson, 1998;Bloom et al, 2010;Crespo Cuaresma et al, 2014b;Prskawetz et al, 2007;Van Der Gaag and De Beer, 2015). A decline in the size of the working age population has a downward effect on GDP per capita, whereas an increase in the number of elderly citizens has an upward effect on costs of pensions and care (Kluge, 2013;Kluge et al, 2018;Van Nimwegen, 2013).…”
Section: Theoretical Considerations and The Proposed Frameworkmentioning
confidence: 99%